Correlates of Mindfulness in Young Adults - Gugel, Tom; Donovan, Zachary; Schneider, Carlee; Geis, Hannah; Felder, Le'Handra; Selvanathan, Hemapreya (My University, 2015)
The purpose of this exploratory study was to examine the relationships between mindfulness in young adults and a large selection of psychological variables. We anticipated inverse correlations between mindfulness and: 1) anxiety, 2) difficulties with emotion regulation, and 3) poor distress tolerance. We anticipated a positive correlation between mindfulness and resilience.
Color poster with text, tables, and graphs.
Keywords: College students; Anti-anxiety techniques; Mindfulness; Posters